Changes in walking strategies after spaceflight. - Bloomberg, J.J.
Over the last several years, our laboratory has investigated postflight astronaut locomotion with the aim of better understanding how adaptive changes in underlying sensorimotor mechanisms contribute to postflight gait dysfunction. One of the first questions we asked focused on the effects of spaceflight on head movement control during postflight locomotion. We hypothesized that adaptive modification in multiple sensorimotor systems caused by exposure to the microgravity conditions of spaceflight would lead to disruption in head-trunk coordination during postflight walking. These changes in head-trunk coordination strategies would then disrupt gaze control and alter the organization of terrestrial locomotor control strategies. The data presented indicate that some behavior observed after spaceflight may represent an adaptive reorganization of motor responses targeted at restoring functional mobility but in a novel way that is not observed or required during preflight walking. This observation has implications for the interpretation of all tests of postflight sensorimotor function.
Keywords: Adaptive changes; Adaptive reorganization; Functional mobility; Gaze control; Head movement control; Head-trunk coordination; Microgravity conditions; Multiple sensorimotor systems; Neuromuscular activation; Postflight astronaut locomotion; Postflight gait dysfunction; Preflight walking; Sensorimotor mechanisms; Spaceflight; Terrestrial locomotor control strategies; Walking strategies